BLOOD VOLUMES OF PAKISTANI MALE DONORS: IMPLICATIONS FOR BLOOD DONATION. - Salamat, Nuzhat (Journal of Ayub Medical College Abbottabad, 2007)
Background: Safety of blood donors rest on withdrawing only appropriate quantities of blood. Adjusting the volumes drawn according to the average blood volumes of any population can ensure this. This requires knowledge of total blood volume of donors, which should ideally be measured by standard methods or derived by alternate suitable method. This observational, cross sectional study was undertaken to calculate blood volumes of Pakistani male donor using recommended equations and obtain safe donation volume limits for our population. Methods: Height and weight of male Pakistani donors reporting to Combined Military Hospital blood bank was recorded by standardized method. Blood volumes were calculated by two different equations using body surface area. The data was entered in SPSS 10.0 version for Windows and statistical analysis done. Results: Mean total blood volumes of 625 ma le donors calculated was 4819.2 ml with first equation and 4566.8 ml with second equation. 95% CI was between 4796.7 and 4841.6 with first equation and 4541.6 and 4591.9 with second equation. The maximum volumes of donation recommended for western population constitutes less than 12 % of calculated total blood volume of our population, with either equation. This is with in safe limits by any standard. Conclusion: 450 ml + 45 ml including samples in pilot tubes should be the recommended donation volume in Pakistani donors. The maximum volume being collected in other countries constitute safe limits for Pakistani donors as well. Equations showing better correlation with measured volumes should preferably be used to calculate blood volumes. Impact of collecting blood volumes recommended in this study, on blood donors, should be studied. Key words: Blood volume; blood donor.